Islamic Teacher's Ethical Behavior, Identity Formation, and Writing Assessment: A Phenomenological Inquiry - Desi Sukenti; Syahraini Tambak (AL-ISHLAH: Jurnal Pendidikan, 2023)
The development of students' academic achievement in the field of Indonesian language is very urgent and for that, a writing assessment is needed. This study uses a phenomenological approach to explore the involvement of Islamic behavior and the identity attribution of Indonesian language teachers in developing writing assessments. Involving twenty Indonesian teachers and conducting in-depth interviews to reveal the narrative of teachers' practices in developing writing assessments. Thematic analysis of two-group interviews with 20 teachers shows that the teacher's Islamic behavior provides a religiously motivated narrative framework that facilitates the interpretation of one's experiences. The involvement of personal morality and religiosity, attribution of identity when assessing, plays a role in the development of writing assessment in the Indonesian language and literature. The application of Islamic behavior principles is the main link in the development of writing assessment, in addition to the attribution of the identity of God-given personality to the assessment of writing Indonesian language and literature. The creativity and writing assessment abilities of Indonesian language teachers develop with various variants, and students' skills and mastery of material also develop in improving literacy, as well as their academic achievements. In conclusion, the results of this exploratory study show that Islamic behavior and personal identity attribution can develop writing assessment in the Indonesian language field. In the future, large-scale research may provide further evidence to reconsider the role of Islamic behavior and attribution of personal identity in teacher training as important factors in the development of Indonesian language teacher writing assessments.